Pengalaman Komunikasi Perempuan dengan Wounded Inner Child dalam Hubungan Romantis (representamen, 2023)
This study discusses the phenomenon of women's communication behavior with wounded inner child in romantic relationships, especially in women with a history of physical and emotional violence in the family. This study was conducted using the phenomenological method to gain an in-depth understanding of the life experiences of women who have a wounded inner child and how it influences their communication behavior in romantic relationships. Data was collected through in-depth interviews with 5 respondents who were adult women with a history of physical or emotional violence in the family. The results of the study show that women with wounded inner child often experience difficulties in communicating in romantic relationships because of various kinds of negative feelings or emotions such as insecurity, low self-esteem, trust issues, anger issues, and others. They often choose to avoid conflict or keep their feelings to themselves, which can lead to bigger conflicts later, or vice versa, namely expressing their feelings with negative or explosive emotional responses in the face of conflict with their partner. The results of this study are expected to contribute to understanding the phenomenon of women's communication behavior with wounded inner child in romantic relationships and can be the basis for developing more effective interventions in helping women who have a history of violence in the family and wounded inner child. Keywords: Communication Behavior, Communication Experience, Wounded inner child.